Nullification of aspirin induced gastrotoxicity and hepatotoxicity by prior administration of wheat germ oil in Mus musculus: histopathological, ultrastructural and molecular studies - Mohamed, H. R. H.; Hamad, S. R. (Cellular and Molecular Biology, 2017)
Aspirin (salicylic acetyl acid) is used worldwide to treat various inflammatory conditions and prevent cardiovascular disease, along with reducing the risk of cancer. However, administration of aspirin causes toxic effects, especially in the stomach and liver. Thus, our study examined the protective effect of wheat germ oil on aspirin-induced toxicity in the stomach and liver tissues of albino white mice. Administration of wheat germ oil before aspirin has restored normal hepatic and gastric tissue architecture and DNA integrity has become better than that of a negative health control group compared with the aspirin only treated group. The elevated gastric nitric oxide content in the aspirin only treated group was significantly decreased by wheat germ oil prior administration as a result of reducedthe expression of inducible nitric synthase and increased the expression of endothelial nitric oxide synthase compared to their expression in the aspirin administered group. Wheat germ oil pre-administration significantly reduced the level of malondialdehyde, increased the level of glutathione and decreased catalase and superoxide dismutase activities compared with those in aspirin only treated group. We conclude that wheat germ oil has a potential protective effect against aspirin induced gastro- and hepato-toxicity because of its free radical scavenging ability.